CYTOPROTECTIVE EFFECTS OF DOPAMINE AND DOBUTAMINE ON ETHANOL-INDUCED GASTRIC LESIONS IN RATS - A. Ömer ÖZÜTEMİZ; Yücel BATUR; Ahmet AYDIN; Oktay TEKEŞİN; Nadir YÖNETCİ; Ahmet MUSOĞLU (Turkish Journal of Gastroenterology, 2020)
-